(untitled) (Research, Society and Development, 2022)
This research aims to understand the constituent bases that underlie the curricular organization through the BNCC’s fields of experience and the guiding assumptions of pedagogical work in Early Childhood Education, in particular those that refer to written language. It is part of a qualitative approach, based on the assumptions of bibliographic research. To this end, works by authors such as Barbosa and Richter, Gimeno-Sacristán and Silva, are used to address curriculum. Vygotsky, Baptista, Leontiev, Jolibert, Lugle & Mello, to support the discussion about written language. It is necessary to take a look at curricular documents, such as: National Curricular References for Early Childhood Education (RCNEI), National Curriculum Guidelines for Early Childhood Education (DCNEI) and National Common Curricular Base (BNCC) to understand the historical course of the curriculum in Early Childhood Education. We deepened the issue of Written Language in the context of the BNCC from the perspective of its organization by Fields of Experience. We understand that highlighting this issue contributes significantly to the work of Early Childhood Education teachers.